2012
DOI: 10.1111/imr.12009
|View full text |Cite
|
Sign up to set email alerts
|

Subversion of cytokine networks by virally encoded decoy receptors

Abstract: Summary During the course of evolution, viruses have captured or created a diverse array of open reading frames that encode for proteins that serve to evade and sabotage the host innate and adaptive immune responses, which would otherwise lead to their elimination. These viral genomes are some of the best textbooks of immunology ever written. The established arsenal of immunomodulatory proteins encoded by viruses is large and growing and includes specificities for virtually all known inflammatory pathways and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
38
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 171 publications
0
38
0
Order By: Relevance
“…Based on the known mechanisms of viral immune evasion, we hypothesized that R17 may function as a viral decoy that prevents chemokine recruitment of immune cells to sites of infection (8). To address the functional consequences of R17-chemokine interactions, we performed experiments evaluating the migration of the human monocytic cell line THP-1 in response to hCCL2, a fast dissociating R17 ligand (K D,eq ϭ 12 nM, t 1/2 ϭ 2.1 s), and human PBMCs in response to hCCL3, a slow off-rate R17 ligand (K D,eq ϭ 1.4 nM, t 1/2,app Ͼ 1,000 s).…”
Section: Production Of Five Secreted Proteins Uniquely Encoded By Rhvpmentioning
confidence: 99%
See 3 more Smart Citations
“…Based on the known mechanisms of viral immune evasion, we hypothesized that R17 may function as a viral decoy that prevents chemokine recruitment of immune cells to sites of infection (8). To address the functional consequences of R17-chemokine interactions, we performed experiments evaluating the migration of the human monocytic cell line THP-1 in response to hCCL2, a fast dissociating R17 ligand (K D,eq ϭ 12 nM, t 1/2 ϭ 2.1 s), and human PBMCs in response to hCCL3, a slow off-rate R17 ligand (K D,eq ϭ 1.4 nM, t 1/2,app Ͼ 1,000 s).…”
Section: Production Of Five Secreted Proteins Uniquely Encoded By Rhvpmentioning
confidence: 99%
“…To function properly, chemokines need to interact with their cognate G protein-coupled receptor as well as glycosaminoglycans (GAGs) on extracellular surfaces where they establish their gradients (9,40). The viral chemokine binding proteins described to date have been shown to interfere with chemokine-GPCR interactions, chemokine-GAG interactions, or both (8). To assess the ability of R17 to block chemokine-GAG interactions, we conducted cell surface binding and competition assays.…”
Section: Production Of Five Secreted Proteins Uniquely Encoded By Rhvpmentioning
confidence: 99%
See 2 more Smart Citations
“…Large DNA viruses usually encode certain viral products to suppress or delay apoptosis of infected cells until abundant progeny viruses are produced (Cuconati and White, 2002;Meseda et al, 2000). Increasing reports showed that viral TNFR homologues were capable of affecting the cellular TNF/TNFR pathway by regulating the host apoptotic response (Benedict et al TNFRs (vTNFRs) can bind to and inhibit the signalling induced by distinct host TNF super family members (Alejo et al, 2011;Epperson et al, 2012). Moreover, vaccinia virus encoded cytokine response modifier E (CrmE) was demonstrated to protect infected cells from apoptosis induced by TNF-a (Graham et al, 2007).…”
Section: Discussionmentioning
confidence: 99%